2021
DOI: 10.1101/2021.09.08.459516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methods for the targeted sequencing and analysis of integrons and their gene cassettes from complex microbial communities

Abstract: Integrons are bacterial genetic elements that can integrate mobile gene cassettes. They are mostly known for spreading antibiotic resistance cassettes among human pathogens. However, beyond clinical settings, gene cassettes encode an extraordinarily diverse range of functions important for bacterial adaptation. The recovery and sequencing of cassettes has promising applications, including: surveillance of clinically important genes, particularly antibiotic resistance determinants; investigating the functional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 77 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…This can be inferred from the phylogeny of IntI protein sequences, which cluster according to the environment of origin rather than bacterial phylogeny. IntIs encoded by marine and soil/freshwater bacteria form the two distinct clades [7,10,16,25]. The same is true for attCs.…”
Section: Environmental Clustering Of Integronsmentioning
confidence: 82%
See 4 more Smart Citations
“…This can be inferred from the phylogeny of IntI protein sequences, which cluster according to the environment of origin rather than bacterial phylogeny. IntIs encoded by marine and soil/freshwater bacteria form the two distinct clades [7,10,16,25]. The same is true for attCs.…”
Section: Environmental Clustering Of Integronsmentioning
confidence: 82%
“…Recent metagenome studies indicate that integrons may indeed be even more diverse than indicated by surveys of sequenced genomes. Analysis of environmental samples has revealed that there are thousands of different integron 'classes' (discerned based on IntI amino acid homology) [25]. Similarly, the gene cassette repertoire of these environmental samples indicates that these elements are abundant and carry a diverse set of genes.…”
Section: Diversity and Distribution Of Integronsmentioning
confidence: 99%
See 3 more Smart Citations